Evaluation of ELISA and Brucellacapt tests for diagnosis of human Brucellosis - Peeridogaheh, Hadi (Tehran University of Medical Sciences, 2013)
BACKGROUND AND OBJECTIVES: Brucellosis is one of the most common zoonotic diseases in Iran and human brucellosis is endemic in all parts of the country. Because of the difficulty in the diagnosis of brucellosis, particularly in endemic areas, the use of new and feasible diagnostic tests seem to be of great importance for resolving the diagnostic obstacles. We evaluated the usefulness of a new serological test based on an immunocapture-agglutination technique in comparison with ELISA test for serological diagnosis of brucellosis. MATERIALS AND METHODS: A total of 11 patients with brucellosis, who had positive blood cultures for Brucella species, and 47 suspected patients were included in this study. Serum samples collected from these patients were tested by brucellacapt and ELISA and the results were, consequently, compared. RESULTS: In patients with positive blood culture, all the samples gave positive results with brucellacapt test while IgM ELISA, IgG ELISA and (IgG + IgM) ELISA tests were positive in 8, 9 and 11 patients, respectively. Out of the 46 suspected patients, (IgG + IgM) ELISA, Brucellacapt, IgG ELISA and IgM ELISA were positive in 37, 15, 34 and 37 patients, respectively.The best cut-off point of ELISA-IgG was 10.78 IU/ml which produced the maximal sensitivity and specificity for the diagnosis of human brucellosis. CONCLUSION: Both the (IgG + IgM) ELISA and Brucellacapt tests demonstrate a high specificity in this study. According to the results of the current study, it is found that both tests are valuable tools for diagnosis of brucellosis in Iran as an endemic area of brucellosis. It is strongly suggested that a combination of both tests to be used for the diagnosis of brucellosis.